Can coffee cultivation lead to food security under a changing climate evidence from Western Honduras - Rodríguez Camayo, Fernando; Ramírez Villegas, Julián Armando; Lundy, Mark M.; Borgermeister, Christian; Beuchelt, Tina (2022)
Understand how coffee value chain actors address food insecurity of coffee households under climate stress.